Untung Rugi Perjanjian Pra-Nikah : Analisis Yuridis Islam Dan Hukum Positif - Ubaidillah, Asep (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2023)
his study aims to analyze the views of Islamic scholars on prenuptial agreements in the perspective of Islamic jurisprudence (fiqh) in Indonesia. The research method used is document analysis of relevant fatwas from various sources, such as official websites of fatwa institutions, fiqh books, and scholarly articles discussing prenuptial agreements. The study shows that Islamic scholars do not oppose prenuptial agreements with certain conditions; in fact, they view it as a way to prevent conflicts by clearly defining the rights and obligations of couples. Although permitted in Islam, agreements must be made in good faith and in accordance with religious values and principles of justice. This study enriches the understanding of the practice of prenuptial agreements in Islam and its relevance in Indonesian Muslim society. The findings are expected to guide the government, prospective couples, and researchers in developing policies and further research related to modern marriage in Indonesia.